Estudio de prefactibilidad para la instalación de una planta procesadora de avena instantánea en polvo - Carrasco Castillo, Mario Francisco (2019)
In the present project, a pre-feasibility study was carried out for the installation of a dry instant oat processing plant whose general objective is to determine its technical, economic and financial viability. The issue arises due to the need to develop research around oats in Peru and thus be able to initiate projects so that the country develops an industry that gives a greater added value to oats. In the market study, the product and the geographical area covered by the project are defined. Then, the historical demand and potential demand are analyzed in order to estimate the specific demand that the project will serve, as well as distribution and commercialization strategies. It was determined that the product will have a presentation of 200 grams of instant powdered oats in polyethylene bags with labeling. The target market will be the population of 25-54 years of NSE A, B, C of Metropolitan Lima. In the plant location chapters, several objective and subjective factors are analyzed to determine the best location of the plant and it was determined that the project will be located in Chilca. Subsequently, in the chapter on plant size, the restrictions established by the market, technology, productive resources and the point of equilibrium are considered. Consequently, it was determined that the plant size is 693,838 bags of instant powdered oats. In the chapter budgets and evaluation of the project, the necessary investments for the project were determined. The total investment required is S /. 471,140, which are composed of tangible fixed assets, fixed intangible assets, working capital and preoperating interests. Finally, the economic and financial evaluation is carried out to determine the feasibility of the project, it was concluded that a Net Economic Actual Value of S /. 115,634 and an Internal Rate of Economic Return of 25.6%, as well as a Net Present Financial Value of S /. 150,122 and an Internal Rate of Financial Return of 32,7%, therefore demonstrating the profitability of the project.